Towards Optimal Disorder in Gold Nanosponges for Long‐Lived Localized Plasmonic Modes. Issue 12 (23rd August 2017) - Schwarz, Felix; Runge, Erich
Abstract: The potential of disorder to confine and enhance electromagnetic fields is well known and localized fields in turn can be used for non‐linear optical sensing and for studying quantum optics. Recently, nanoporous gold nanoparticles (nanosponges) were shown to support highly localized long‐lived plasmonic modes in the infrared spectral range. In this paper, we take first steps towards tailoring the disorder for optimal field localization and enhancement by calculating extinction and near‐field properties for different filling fractions and correlation lengths. We find that the filling fraction has not only a large effect on the fundamental dipolar surface‐plasmon resonance of the nanoparticle, but also on the frequency range in which localized modes of plasmonic nature occur. The influence of the correlation length is more subtle but is seen to influence the coupling between localized and far‐field modes as well. We briefly discuss first results on details of the localization process, which takes place on the same length scale as the typical structure size, so a simple cavity‐resonance picture cannot account for the relatively low frequency of the modes. Abstract : Nanoporous gold nanoparticles (nanosponges) intrinsically confine and enhance electromagnetic fields as plasmonic modes on a length scale given by the pore size, which is well below optical wavelengths. This opens new routes towards, e.g., non‐linear optical sensing and nano‐scale quantum optics. A numerical study varies filling fractions and feature size of the gold sponges in order to understand and optimize the presence of long‐lived ultra‐localized plasmonic modes.